2021
DOI: 10.1093/ntr/ntab093
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Strong Enforcement: Understanding the Factors Related to Retailer Compliance With Tobacco 21

Abstract: Introduction Tobacco 21 (T21), which sets the minimum legal sales age for tobacco to age 21, is now a national law in the U.S. Although T21 is expected to help curb youth tobacco use, its impact may be dampened due to poor retailer compliance. Even within environments where enforcement is strong (i.e., compliance checks are conducted with tough sanctions for violations), compliance might vary due to other factors. Methods Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Among those aged 18 to 20 years, we found that state T21 policies were protective against cigarette smoking among White young adults but not among those of racial or ethnic minority groups. These findings are consistent with previous research showing weaker age verification enforcements among minority populations ( 2 , 16 , 21 ). Several factors may account for these differences in tobacco access and use, including differences in accessibility to small retail stores where age verification is less likely to be enforced, such as liquor stores, gas stations, corner stores, small kiosks, and convenience stores ( 7 , 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…Among those aged 18 to 20 years, we found that state T21 policies were protective against cigarette smoking among White young adults but not among those of racial or ethnic minority groups. These findings are consistent with previous research showing weaker age verification enforcements among minority populations ( 2 , 16 , 21 ). Several factors may account for these differences in tobacco access and use, including differences in accessibility to small retail stores where age verification is less likely to be enforced, such as liquor stores, gas stations, corner stores, small kiosks, and convenience stores ( 7 , 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…38 41 found that displaying T21 signs was strongly associated with ID checks among retailers. 41 In Cleveland, this would suggest that the areas with low signage adherence may also be areas with low sales adherence, which may alter the longterm trajectories of youth tobacco use if these disparities persist.…”
Section: Discussionmentioning
confidence: 99%
“…Posting policy-relevant signs helps to foster population norms by promoting awareness by customers, store owners, managers, and employees. A 2021 study by Roberts et al 41 found that displaying T21 signs was strongly associated with ID checks among retailers. 41 In Cleveland, this would suggest that the areas with low signage adherence may also be areas with low sales adherence, which may alter the long-term trajectories of youth tobacco use if these disparities persist.…”
Section: Discussionmentioning
confidence: 99%
“…The limited research on age of sale compliance is mixed but suggests that T21 is not enforced uniformly. 1 , 2 , 3 Moreover, current compliance protocols have methodological limitations that limit validity. 4 A familiarity protocol that mimics actual purchasing behaviors is recommended, including repeated visits to the same store with the same buyer.…”
Section: Introductionmentioning
confidence: 99%